Autumn, the neglected season in climate change research. (March 2015) - Gallinat, Amanda S.; Primack, Richard B.; Wagner, David L.
Highlights: Climate change in autumn shifts times of leaf fall, bird migration, and other events. These shifts change carbon dynamics and can favor invasive species and pathogens. Vulnerable species may be harmed by changing ecological interactions in the autumn. Experiments and new datasets are crucial for improved modeling and management. Abstract : Autumn remains a relatively neglected season in climate change research in temperate and arctic ecosystems. This neglect occurs despite the importance of autumn events, including leaf senescence, fruit ripening, bird and insect migration, and induction of hibernation and diapause. Changes in autumn phenology alter the reproductive capacity of individuals, exacerbate invasions, allow pathogen amplification and higher disease-transmission rates, reshuffle natural enemy–prey dynamics, shift the ecological dynamics among interacting species, and affect the net productivity of ecosystems. We synthesize some of our existing understanding of autumn phenology and identify five areas ripe for future climate change research. We provide recommendations to address common pitfalls in autumnal research as well as to support the conservation and management of vulnerable ecosystems and taxa.